Cognitive Health for older adults who live with their families and peers at nursing homes - Al-Abadi, Adel (Al-Adab Journal, 2025)
The current research aims to: built scale to measure cognitive health older adults, measure cognitive health older adults who live with their families and peers at nursing homes ,and Defining differences in cognitive health according to gender (males – females ) To achieve these objectives, the researcher built Scale to measure cognitive health older adults,  The final form of this measurement after the completion of the conditions such as validity, constancy, and the ability for discrimination has consisted of( 27) items ,were  prepared  for a sample  of (200)  older  adults,  and  data is  dealtStatistically by means of (SPSS) and The study reached the following results: Achieve built scale to measure cognitive health older adults,  The older adults who live with their families  have cognitive health and the older adults not have a cognitive health, There are differences by gender in favor of males in the older adults with their families in the cognitive health while - There are no differences by sex (male - female) in the older adults role of shelter and the older adults with their families in the cognitive health In light of the current research results, the researcher made several recommendations and suggestions.such as study the cognitive health with social support ,quality of life ,active personality ,psychological well-being  and  social marginalization.